Menorah under the sea - Heller, Esther Susan (Minneapolis, MN : Kar-Ben Pub., 2009)
Describes how marine biologist David Ginsburg celebrated the first night of Hanukkah while studying sea urchins in Antarctica.
Publisher's Weekly
School Library Journal
Publisher's Weekly, October 2009
School Library Journal, September 2009
5.1
K-3
Keywords: Hanukkah -- Juvenile literature; Marine biologists -- Antarctica -- Juvenile literature; Hanukkah; Marine biologists; Hanukkah; Marine biologists; Antarctica -- Juvenile literature; Antarctica; Antarctica